Penilaian Manfaat Pelabuhan Nonkomersial Pada Wilayah Tertinggal Kabupaten Aceh Singkil - Sukwika, Tatan (Jurnal Ekonomi & Kebijakan Publik, 2024)
The role of non-commercial ports as cross-island connectivity is very important in disadvantaged regions. However, common problems at non-commercial ports in Singkil Regency are inadequate and insufficient facilities for port operational activities, and very little passenger and goods ships traffic to and from Singkil Port. So that the development of non-commercial port service activities does not show that it has been used optimally. This study focuses on the benefits of sea transportation infrastructure in disadvantaged regions built with the state budget (APBN). This study aims to evaluate the value of the benefits of infrastructure development based on aspects and indicators of port development. The method of measurement and assessment of aspects and indicators used a quantitative approach and descriptive analysis. Data collection through field observation and interviews, as well as a secondary data desk study. The results of the research show that the benefits of port development are sufficient or do not provide optimal benefits. The perceived benefits of port infrastructure development can be identified from economic, social demographic and transportation aspects, both directly and indirectly. The policy implication is that port managers need to cooperate with port service users to revive port activities, especially economic activity around the port.AbstrakPeran pelabuhan nonkomersial sebagai konektivitas lintas pulau sangat penting di daerah tertinggal. Di lain sisi, permasalahan umum pada pelabuhan nonkomersial di Kabupaten Singkil yaitu fasilitas kegiatan operasional pelabuhan tidak dicukupi dan tidak memadai, serta trafik kapal penumpang dan barang dari dan ke Pelabuhan Singkil sangat sedikit, sehingga pengembangan aktivitas pelayanan pelabuhan nonkomersial tidak menunjukkan telah termanfaatkan secara optimal. Kajian ini difokuskan pada manfaat infrastruktur transportasi laut di wilayah tertinggal yang dibangun dengan Anggaran Pendapatan dan Belanja Negara (APBN). Penelitian bertujuan mengevaluasi nilai manfaat pembangunan infrastruktur berdasarkan aspek pembangunan pelabuhan dan indikator-indikatornya. Metode pengukuran dan penilaian aspek dan indikator menggunakan pendekatan kuantitatif dan analisis deskriptif. Pengumpulan data melalui metode observasi lapangan dan wawancara, serta desk-study data sekunder. Hasil penelitian menunjukkan bahwa nilai manfaat pembangunan pelabuhan adalah bernilai cukup artinya manfaat pembangunan pelabuhan belum termanfaatkan secara optimal. Manfaat pembangunan infrastruktur pelabuhan yang dirasakan dapat diidentifikasi secara ekonomi, sosial kependudukan dan transportasi, baik langsung maupun tidak langsung. Implikasi kebijakannya adalah pengelola pelabuhan perlu berkerja sama dengan pengguna jasa pelabuhan untuk menghidupkan aktivitas pelabuhan, khususnya kegiatan ekonomi di sekitar pelabuhan.